Factor Selection in Drilling Unidirectional Carbon Fiber Reinforced Plastic Composite Plates with The HSS Drill Bit Using Analytic Hierarchy Process - Oke, Sunday Ayoola; Odusoro, Salome Ifeoluwa (International Journal of Industrial Engineering and Engineering Management, 2021)
The present state of competition within the plastic composite industry calls for efficiency to be competitive. However, in the drilling of carbon-fiber-reinforced plastic (CFRP) composites, the process engineer still lacks knowledge of the priority of parameters as parameters are chosen at random, and resources are deployed without justification on their importance and strength. Consequently, production crises and productivity losses persist. In this article, the analytic hierarchy process (AHP) method is deployed to evaluate the weights of criteria in a CFRP composite drilling operation. The establishment of the decision, alternatives, and criteria is accomplished, and pairwise comparisons are conducted to allow the computation of the importance weight of each criterion. The weight is then established. The proposed approach was illustrated with experimental data from the literature with a plastic drilling case. Six criteria were chosen as crucial in determining the drilling parameters of CFRP composites. The results reveal the following: thrust force (0.413), torque (0.253), eccentricity (0.151), surface roughness (0.115), delamination at entry (0.037) and delamination at exit (0.030). In a validation exercise to ascertain the consistency of the analysis, a consistent analysis was obtained. The novelty of the article is using the AHP approach on the drilling of CFRP composites. Practically, these results impact operator training, indicating that attention should be focused on thrust force control. The industrial applications of CFRP composites include the basic structures of automobiles, ships, and airplanes.